Next‐Generation Sequencing Assessment of Eukaryotic Diversity in Oil Sands Tailings Ponds Sediments and Surface Water. (2nd May 2016) - Aguilar, Maria; Richardson, Elisabeth; Tan, BoonFei; Walker, Giselle; Dunfield, Peter F.; Bass, David; Nesbø, Camilla; Foght, Julia; Dacks, Joel B.
Abstract: Tailings ponds in the Athabasca oil sands (Canada) contain fluid wastes, generated by the extraction of bitumen from oil sands ores. Although the autochthonous prokaryotic communities have been relatively well characterized, almost nothing is known about microbial eukaryotes living in the anoxic soft sediments of tailings ponds or in the thin oxic layer of water that covers them. We carried out the first next‐generation sequencing study of microbial eukaryotic diversity in oil sands tailings ponds. In metagenomes prepared from tailings sediment and surface water, we detected very low numbers of sequences encoding eukaryotic small subunit ribosomal RNA representing seven major taxonomic groups of protists. We also produced and analysed three amplicon‐based 18S rRNA libraries prepared from sediment samples. These revealed a more diverse set of taxa, 169 different OTUs encompassing up to eleven higher order groups of eukaryotes, according to detailed classification using homology searching and phylogenetic methods. The 10 most abundant OTUs accounted for > 90% of the total of reads, vs. large numbers of rare OTUs (< 1% abundance). Despite the anoxic and hydrocarbon‐enriched nature of the environment, the tailings ponds harbour complex communities of microbial eukaryotes indicating that these organisms should be taken into account when studying the microbiology of the oil sands.